POTENSI EKONOMI SYARIAH DENGAN TREN HALAL LIFESTYLE DI INDONESIA DALAM PERSPEKTIF STATE THE GLOBAL ISLAMIC ECONOMY REPORT (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2021)
This article aims to find out how the potential of the sharia economy is with the trend of halal lifestyle in Indonesia in the perspective of the State the Global Islamic Economy Report. This article is a descriptive qualitative research article with a literature research approach using secondary data obtained through scientific articles and other relevant documents. The data collection in this article is carried out through the official website www.salaamgateway.com regarding the position of Indonesia in the State the Global Islamic Economy Report. The results of this article show that the top 20 countries with global capital and asset figures, private equity, and venture capital investment in consumers , which was released by the SGIER 2020/2021 shows that the position of the Indonesian state is in the first position in the absorption of world halal products, and sequentially from 2018/2019 and 2019/2020. With the presentation of the data that has been submitted, regarding countries that absorb world halal products, that the country of Indonesia is a country that has enormous potential to absorb world halal products, especially in halal food and beverage products. This condition can be a reference for stakeholders to pursue steps, strategies and policies to realize Indonesia as the center of the world's halal supply chain. Keywords: Sharia Economic Potential, Halal Lifestyle, Global Islamic Economy Report